ARCHETYPAL IMAGES REFLECTED IN DRACULA NOVEL BY BRAM STOKER - Yulia Puspita Sari; Emil Eka Putra (Universitas Putera Batam, 2021)
This research discusses archetypal in the novel Dracula written by Stoker. The purpose of this research is to find out some archetypal images in the novel. Some of the problems that exist today are readers who do not know the meaning of archetypal images contained in a novel. The data used in this study were taken from the novel Dracula written by Stoker. In this research, the researcher applies Carl Jung's theory. This study uses descriptive qualitative research, in qualitative research the key concepts, ideas, and processes studied are part of the central phenomenon. The result of this research is that the novel Dracula has many archetypal images contained in it. The archetypes in Dracula are: sun, color, the archetype women, and wise old man. Based on the results of this study, the researcher concludes that there are several archetypes in Dracula's novel that are used to convey implied meanings through the symbols used.